Strengthening the Creative Economy through Rambutan Kombucha Training in Kalongan Village - Natalie Beth Evangeline Alficorista; Sulaeman Fityan Saputra; Shafwa Marine Pasekoenda; Fadiyah Salsabila; Citra Pramesti; Bienda; Salsa Mayllanie Putri; Qonita Farah Hayuningtyas; Elora Sabina; Christian Raymundo Sampayan (Carmin: Journal of Community Service, 2026)
The problem addressed in this community service activity was the limited utilization of rambutan commodities in Kalongan Village, which were generally consumed directly or sold in fresh form without further processing, resulting in low economic value. Therefore, this program aimed to strengthen the local creative economy through training on rambutan kombucha production as an innovative fermented beverage product. The activity was conducted in Kalongan Village, East Ungaran District, Semarang Regency, involving 40 members of the Family Welfare Empowerment (PKK) group and local residents. The program applied the Participatory Action Research (PAR) approach through stages of socialization, practical training, mentoring, and evaluation. Evaluation instruments included pre-test and post-test assessments, observation sheets, and participant response questionnaires analyzed descriptively using percentage analysis. The results showed that the average participant score increased from 56.8 to 84.5, indicating a 48.77% improvement in knowledge and understanding of fermentation techniques, sanitation procedures, and creative economy concepts. In addition, 87.5% of participants were able to independently practice the fermentation process, while 82.5% positively accepted the product based on sensory evaluation. The kombucha product achieved an average pH value of 3.2 after 8 days of fermentation, indicating acceptable fermentation quality and safety standards. Furthermore, 77.5% of participants expressed interest in developing rambutan kombucha as a small-scale household business. The program produced several outputs, including a rambutan kombucha prototype, an educational e-module, and a scientific publication draft. Overall, the RAMBUSA program contributed to improving community skills, optimizing local commodity utilization, and supporting sustainable village-based creative economy development.